EXPLORING ECONOMIC AND SPATIAL DEPENDENCIES OF CRIME RATES IN EUROPE AT THE NUTS-3 LEVEL - Penchev, Georgi Georgiev (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The paper is focused on the spatial exploratory analysis of data related to crime and economic development in EU on the NUTS-3 level. NUTS is the statistical territorial classification of EU and EUROSTAT and its 3rd level includes the smallest regions. The analysis has three steps. First of all, the most commonly used indicators in studies investigating the relationship crime-economic conditions were identified. In the second stage, after search for these indicators in EUROSTAT NUTS-3 level datasets the research dataset was established. Finally, the data is geographically referenced and tests for spatial dependencies and local correlation of some indicators are introduced. Hierarchical clustering of indicators is used both for 2009 and 2010. The research shows the existence of flows and inequalities of data, as well as absence of data on NUTS-3 level for important indicators, despite their presence on higher levels of the territorial classification. Regardless of these shortcomings, the exploratory spatial analysis generates the idea to continue the research on the relations between infrastructural indicators such as distance to ports and highways and crime rates. The mapping of identified clusters shows the existence of stable geographically formed groups of regions from similar clusters. Another positive result is the possibility to classify, visualize and study the similarities and differences in EU smallest statistical regions.